Impact of Pituitary–Gonadal Axis Hormones on Pulmonary Arterial Hypertension in Men. Issue 1 (July 2018) - Wu, Wen-Hui; Yuan, Ping; Zhang, Si-Jin; Jiang, Xin; Wu, Cheng; Li, Yuan; Liu, Shao-Fei; Liu, Qian-Qian; Li, Jing-Hui; Pudasaini, Bigyan; Hu, Qing-Hua; Dupuis, Jocelyn; et al.
Abstract : The association of sex hormone (estradiol, testosterone, and progesterone) with cardiopulmonary disease has already attracted great attention, especially in pulmonary arterial hypertension (PAH). However, the impact of sex hormones and their pituitary stimulators (follicle-stimulating hormone and luteinizing hormone) on PAH in men remains unclear. We conducted a prospective cohort study recruiting 95 patients with idiopathic PAH from 2008 to 2014 and following up for a median of 65 months for death. Compared with control, abnormal plasma levels of sex hormones were more common in patients with PAH. Higher estradiol and estradiol/testosterone levels were associated with risk of PAH diagnosis (odds ratio per ln estradiol, 3.55; P <0.001; odds ratio per ln estradiol/testosterone, 4.30; P <0.001), whereas higher testosterone and progesterone were associated with a reduced risk (odds ratio per ln testosterone, 0.48; P =0.003; odds ratio per ln progesterone, 0.09; P <0.001). Fifty patients died during follow-up. Men with higher estradiol had increased mortality (hazard ratio per ln estradiol, 2.02; P =0.007), even after adjustment for baseline characteristics and PAH treatment. According to receiver operating characteristic analysis, patients with PAH with higher estradiol level (≥145.55 pmol/L) had worse 5-year survival rate compared with those with lower estradiol (38.6% versus 68.2%; log-rank test P =0.001). Therefore, our data show higher estradiol, estradiol/testosterone ratio, lower testosterone, and progesterone were associated with increased risk of PAH. Meanwhile, higher estradiol was independently associated with higher mortality in men with PAH. Further studies are needed to explain the origin of these hormonal derangements and their potential pathophysiological implications in PAH. Abstract : Supplemental Digital Content is available in the text.